2022
DOI: 10.3390/antiox11071254
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Roles of Oxidative Stress in Triangular Relationships among Arthropod Vectors, Pathogens and Hosts

Abstract: Blood-feeding arthropods, particularly ticks and mosquitoes are considered the most important vectors of arthropod-borne diseases affecting humans and animals. While feeding on blood meals, arthropods are exposed to high levels of reactive oxygen species (ROS) since heme and other blood components can induce oxidative stress. Different ROS have important roles in interactions among the pathogens, vectors, and hosts. ROS influence various metabolic processes of the arthropods and some have detrimental effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…It has been proven that ticks during blood meals are displayed significant amount of reactive oxygen species (ROS) because of presence of some blood elements which can provoke oxidative stress and subsequently damage ticks (Hernandez at al., 2022). A normal harmony amongst production of ROS production (oxidative stress) and its deactivation (antioxidant) strengthens survival and ticks abilities and inhibits the effects of acaricidal agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proven that ticks during blood meals are displayed significant amount of reactive oxygen species (ROS) because of presence of some blood elements which can provoke oxidative stress and subsequently damage ticks (Hernandez at al., 2022). A normal harmony amongst production of ROS production (oxidative stress) and its deactivation (antioxidant) strengthens survival and ticks abilities and inhibits the effects of acaricidal agents.…”
Section: Resultsmentioning
confidence: 99%
“…A normal harmony amongst production of ROS production (oxidative stress) and its deactivation (antioxidant) strengthens survival and ticks abilities and inhibits the effects of acaricidal agents. Thus, a potent acaricidal agent by disturbing this balance through decreasing the antioxidant activities and increasing oxidative stress can cause serious damage to the critical organisms of ticks (Hernandez at al., 2022). We found that after the exposure of H. dromedarii larvae to SNP, especially at ½ LC50 and LC50, markedly (p<0.001) increased the MDA level; on the other hand, (p<0.001) declined the level of GST in H. dromedarii larvae (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, antioxidant defense is crucial in combating reactive oxygen species (ROS) and protecting the cell from oxidative damage caused by ROS (Hernandez et al 2022).…”
Section: Discussionmentioning
confidence: 99%